Analysis of Students' Difficulties in Solving Fraction Subtraction Problems in Fourth Grade Elementary School - Roheni, Roheni (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This study aims to analyze the difficulties faced by fourth-grade elementary school students in solving fraction subtraction problems. The research method used is qualitative with a descriptive approach. The study sample consisted of 30 fourth-grade students from SD Negeri 1 Megu Gede, selected using a purposive sampling technique. Data were collected through an essay test designed to assess students' ability to perform fraction subtraction operations. The results indicated that most students struggled with fraction subtraction problems, particularly when dealing with unlike denominators. The primary mistake observed was students subtracting denominators directly, revealing a lack of conceptual understanding of fractions. Additionally, students had difficulty determining the Least Common Multiple (LCM), a crucial step in equalizing denominators before performing subtraction. Contributing factors to these difficulties include conventional teaching methods, limited use of concrete teaching aids, and a lack of contextual problem-solving exercises. These findings highlight the importance of implementing more interactive and experience-based teaching strategies, such as visual and manipulative media, to enhance students' understanding of fractions. Improving teaching methods is expected to help students better grasp fraction subtraction concepts and minimize conceptual errors.